Advancing theoretical understanding and practical performance of signal processing for nonlinear optical communications through machine learning - Qirui Fan (Nature Portfolio, 2020)
Nonlinear effects provide inherent limitations in fiber optical communications. Here, the authors experimentally demonstrate improved digital back propagation with machine learning and use the results to reveal insights in the optimization of digital signal processing.